ATARAXIA DAN SHALOM: KOMPARASI KONSEP BAHAGIA STOIK DENGAN AJARAN YESUS KRISTUS - setiabudi, Hengki irawan (Sekolah Tinggi Teologi Pelita Hati, 2025)
This study explores and compares the concept of happiness in Stoic philosophy and the teachings of Jesus, focusing on the idea of “Ataraxia” in Stoicism and “Shalom” in the Judeo-Christian tradition. The study aims to analyze the differences and similarities between the two views, as well as their implications for contemporary understandings of happiness. Through textual analysis of classical Stoic writings and the New Testament, the study investigates how these two traditions understand the source, nature and attainment of happiness. Stoicism emphasizes Ataraxia as a state of inner calm achieved through self-acceptance and mastery, while the teachings of Jesus promote Shalom as a holistic peace rooted in relationships with God and others. Preliminary findings suggest that despite significant differences in metaphysical foundations and ultimate goals, both traditions offer valuable insights into the role of acceptance, wisdom and transcendence in the attainment of true happiness. This research contributes to the dialogue between classical philosophy and Christian theology, while offering new perspectives for understanding and pursuing happiness in a modern context.